The effects of graft source and orientation on outcomes after ablation of a branched peripheral nerve - Allgood, JuliAnne E.; Roballo, Kelly C. Santos; Sparks, Bridger B.; Bushman, Jared S. (Frontiers in Cellular Neuroscience, 2022)
Segmental peripheral nerve injuries (PNI) are the most common cause of enduring nervous system dysfunction. The peripheral nervous system (PNS) has an extensive and highly branching organization. While much is known about the factors that affect regeneration through sharp bisections and linear ablations of peripheral nerves, very little has been investigated or documented about PNIs that ablate branch points. Such injuries present additional complexity compared to linear segmental defects. This study compared outcomes following ablation of a branch point with branched grafts, specifically examining how graft source and orientation of the branched graft contributed to regeneration. The model system was Lewis rats that underwent a 2.5 cm ablation that started in the sciatic nerve trunk and included the peroneal/tibial branch point. Rats received grafts that were rat sciatic autograft, inbred sciatic allograft, and inbred femoral allograft, each of which was a branched graft of 2.5 cm. Allografts were obtained from Lewis rats, which is an inbred strain. Both branches of the sciatic grafts were mixed motor and sensory while the femoral grafts were smaller in diameter than sciatic grafts and one branch of the femoral graft is sensory and the other motor. All branched grafts were sutured into the defect in two orientations dictated by which branch in the graft was sutured to the tibial vs peroneal stumps in recipients. Outcome measures include compound muscle action potentials (CMAPs) and CatWalk gait analysis throughout the recovery period, with toluidine blue for intrinsic nerve morphometry and retrograde labeling conducted at the 36-week experimental end point. Results indicate that graft source and orientation does play a significant role earlier in the regenerative process but by 36 weeks all groups showed very similar indications of regeneration across multiple outcomes.